Sharing knowledge and building communities in signal processing. - Baraniuk, R.G (IEEE Signal processing magazine)
There is a great need for information technologies for developing and delivering quality, up-to-date educational materials that convey to all learners that knowledge is a dynamic continuum that stretches across disciplines. To address this need, an experimental, open-source/open-content initiative, called the Connexions Project, was initiated. The Connexions Project offers an alternative to the way textbooks and other learning materials are created, maintained, and used. By design, Connexions greatly impacts current modes of teaching and learning, and the development and sharing of knowledge. In combination with powerful software tools which consist of an XML language, Connexions gives learner free access to educational materials that can be readily manipulated to suit their individual learning styles as they explore links among concepts. The free software tools also foster the development, manipulation, and continuous refinement of educational material by diverse communities of authors and instructor. An overview of the philosophy and progress of the project is presented, with a particular emphasis on its application to the area of signal processing.